NGOs, agencies and donors in participatory conservation: lates from Nagarahole - Mahanty, Sanghamitra (2002)
With much of the emphasis in recent discussions on India's parks being on issues of community participation, this paper instead directs its attention to how the internal dynamics of government agencies and the relationships between NGOs, agencies and donors can influence the conduct of conservation programmes. These issues are examined through a case study of the India Ecodevelopment Project at Rajiv Gandhi National Park. While the emphasis in this paper is on the ecodevelopment programme, it raises wider issues for park management in India. - Reproduced.
Keywords: Nongovernmental organizations; Parks